Teacher training program for medical students: improvements needed - van Diggele C; Burgess A; Mellis C (Advances in Medical Education and Practice, 2015)
Christie van Diggele,1 Annette Burgess,2 Craig Mellis21The University of Sydney, Sydney, NSW, Australia; 2Sydney Medical School – Central, The University of Sydney, Sydney, NSW, AustraliaIntroduction: Skills in peer teaching, assessment, and feedback are increasingly documented internationally as required graduate attributes in medicine. Yet these skills are rarely taught in medical schools. We sought to design and deliver a short but effective teacher training (TT) program for medical students that could be easily integrated into the professional development curriculum. This study sought to evaluate such a pilot program, based on student perception.Methods: The study took place at a major metropolitan teaching hospital, where 38 medical students were invited to attend a voluntary, newly designed four-module TT program. In total, 23/38 (61%) of invited students attended. Mixed methods were used for evaluation. Questionnaires were completed by 21/23 (91%) of students, and 6/23 (26%) of students participated in a focus group.Results: Students reported that as a result of the program they felt more confident to facilitate small group teaching activities and to provide feedback to peers using the suggested frameworks. Students would like the program to contain more in-depth educational theory and to allow a more time for small group learning activities. They would also like to see opportunities for participation across all clinical schools.Conclusion: The TT program was successful in increasing student awareness of educational theory and practice, thereby improving their confidence in teaching and assessing their peers and making them feel better prepared for their careers as medical practitioners. Key improvements to the program are needed in terms of more in-depth theory and more time spent on small group learning. This might be achieved by complementing the course with e-learning.Keywords: teacher training, medical students, peer teaching, peer assessment